Dimagi : Improving Maternal and Newborn Care - Agapitova, Natalia (World Bank, Washington, DC, 2017)
India suffers from a high maternal and infant mortality rate, especially in rural areas, where poor women do not receive effective care and one in every 22 infants die within one year of life. In 2010, Dimagi, in partnership with Catholic Relief Services (CRS), IntraHealth International, Real Medicine Foundation, and Save the Children, deployed CommCare mobile technology to help Accredited Social Health Activists (ASHAs) improve their care for pregnant women and their newborns at the last mile in rural India. CommCare uses audio, video, imagery, short message service (SMS) texting, data and tracking forms, multiple languages, and other features to standardize ASHAs’ service delivery, improve counseling techniques and patient coordination, and collect real-time data for performance monitoring. The multimedia aids enhance client engagement and assist low-literate ASHAs and their clients. Through a partnership with the Government of India and the Bill and Melinda Gates Foundation, a CommCare-based application is being scaled across eight Indian states to strengthen the monitoring of the service delivery of anganwadi center’s in the country. The CommCare mobile application is intended to replace the extensive paper registers anganwadi workers are required to maintain. The app is designed to improve the care anganwadi workers provide their communities, tracking distribution of immunizations and supplementary food, attendance of children at preschool, and the nutrition status of children up to age five.